2017
DOI: 10.18632/oncotarget.21914
|View full text |Cite
|
Sign up to set email alerts
|

PD-1/PD-L1 interaction up-regulates MDR1/P-gp expression in breast cancer cells via PI3K/AKT and MAPK/ERK pathways

Abstract: Programmed cell death ligand 1 (PD-L1) is an immunosuppressive molecule expressed on tumor cells. By interacting with programmed cell death-1 (PD-1) on T cells, it inhibits immune responses. Because PD-L1 expression on cancer cells increases their chemoresistance, we investigated the correlation between PD-L1 and multidrug resistance 1/ P-glycoprotein (MDR1/P-gp) expression in breast cancer cells. Analysis of breast cancer tissues using tissue microarrays revealed a significant correlation between PD-L1 and MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 44 publications
(41 reference statements)
2
65
0
Order By: Relevance
“…Recruitment of SHP2 to the ITIM and ITSM cytoplasmic domains of PD-1 inhibits PI3K thus further blocks AKT phosphorylation and mTOR pathway ( 101 ). It is important to note that reports from cancer studies suggest that PD-1 engagement with PD-L1 does not cause dephosphorylation, but leads to phosphorylation and activation of AKT and ERK, which increases chemo resistance of the cancer cells ( 102 , 103 ), implying a difference in PD-1 signaling between chronic infection and cancer that requires further investigation. Through inhibiting these signaling molecules, PD-1 indirectly inhibits the production of cytokines including IL-2, hence interferes with T cell growth and function.…”
Section: Signaling Pathways and T-cell Exhaustionmentioning
confidence: 99%
“…Recruitment of SHP2 to the ITIM and ITSM cytoplasmic domains of PD-1 inhibits PI3K thus further blocks AKT phosphorylation and mTOR pathway ( 101 ). It is important to note that reports from cancer studies suggest that PD-1 engagement with PD-L1 does not cause dephosphorylation, but leads to phosphorylation and activation of AKT and ERK, which increases chemo resistance of the cancer cells ( 102 , 103 ), implying a difference in PD-1 signaling between chronic infection and cancer that requires further investigation. Through inhibiting these signaling molecules, PD-1 indirectly inhibits the production of cytokines including IL-2, hence interferes with T cell growth and function.…”
Section: Signaling Pathways and T-cell Exhaustionmentioning
confidence: 99%
“…CRISPR/Cas9 system-mediated PD-L1 disruption increased drug sensitivities for doxorubicin and paclitaxel ( 90 ). The interaction of PD-L1 with PD-1 induced phosphorylation of AKT and ERK, resulting in the activation of PI3K/AKT and MAPK/ERK pathways and increased MDR1 expression in breast cancer cells ( 101 ).…”
Section: The Role Of Pd-l1 In Stimulating or Inhibiting Cancermentioning
confidence: 99%
“…PD-L1 is highly expressed in many malignant tumors ( 18 , 19 ). Studies have shown that PD-L1 may be regulated by oncogenes and various signaling pathways ( 20 23 ). High expression of PD-L1 can reduce the immune effect of T cells in the local microenvironment of the tumor, thus facilitating tumor escape and promoting tumor growth ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%